Reliable and simple analytical methods for determination of citrulline and metabolically related amino acids by liquid chromatography after derivatization: comparison between monolithic and core–shell columns - Acquaviva, Agustín (2014)
We describe the development of a high-performance liquid chromatography (HPLC) method for the determination of citrulline and other amino acids relevant to intestinal diseases. The amino acids were derivatized with 9-fluorenylmethylchloroformate (FMOC-Cl) and their derivatives were separated on two different columns, a core-shell column (Halo C18) and a silica-based monolith (Chromolith Performance RP-18). The derivatization reaction was optimized with respect to pH, buffer concentration and reproducibility. The optimal derivatization conditions were achieved with 0.4 M borate buffer at pH 9.20, a constant ratio of FMOC-Cl/total amino acids (10 : 1) and 75 mM tyramine after 1 min (quenching reaction). The separation conditions with both chromatographic supports were also optimized. The chromatographic performance (peak capacity and global resolution) of these two columns was compared. This proposed HPLC-UV method was satisfactorily applied to the analysis of a real plasma sample. © 2014 The Royal Society of Chemistry.